2019
DOI: 10.3390/en12091710
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Modern Power System: Real-Time Power Balancing through Load and Wind Power

Abstract: Increasing large-scale integration of renewables in conventional power system has led to an increase in reserve power requirement owing to the forecasting error. Innovative operating strategies are required for maintaining balance between load and generation in real time, while keeping the reserve power requirement at its minimum. This research work proposes a control strategy for active power balance control without compromising power system security, emphasizing the integration of wind power and flexible loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The results demonstrated the ability of DR control loop for LFC performance in the SG perspective. An active power balance control strategy that stressed the integration of flexible loads and wind energy in AGC is suggested in [112]. The study revealed that the incorporation of flexible loads and wind power into the AGC system can eradicate the fluctuations via provisioning of active power support to the real-time imbalances.…”
Section: Agc In Smart Gridsmentioning
confidence: 99%
“…The results demonstrated the ability of DR control loop for LFC performance in the SG perspective. An active power balance control strategy that stressed the integration of flexible loads and wind energy in AGC is suggested in [112]. The study revealed that the incorporation of flexible loads and wind power into the AGC system can eradicate the fluctuations via provisioning of active power support to the real-time imbalances.…”
Section: Agc In Smart Gridsmentioning
confidence: 99%
“…In [7], the impact of flexible load and wind power integration on power system imbalance is discussed. Cold storage rooms are considered as flexible loads as they can provide demand response.…”
Section: Related Workmentioning
confidence: 99%
“…The power system planners employ various scheduling mechanisms to deploy the extra amount of reserve, keeping the power grids in a balance condition. Conventionally, the additional reserves are provided manually or through automatic generation control (AGC) considering only the economic operation in the account [2]. As a result, large fluctuations in the line power flow occur, which subsequently increases the risk of transmission lines overloading during the power balancing operation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%